The role of cholesterol metabolism in multiple sclerosis: From molecular pathophysiology to radiological and clinical disease activity - Lorincz, Balazs; Jury, Elizabeth C; Vrablik, Michal; Ramanathan, Murali; Uher, Tomas (Autoimmunity reviews, 2022)
Multiple sclerosis (MS) is a chronic inflammatory disease of the CNS leading to demyelination and axonal degeneration. An increasing body of evidence suggests that lipid metabolism is associated with adverse clinical and MRI outcomes in MS. In this review we summarize the findings of association between low-density lipoproteins (LDL), high-density lipoproteins (HDL), their apolipoproteins and oxysterols with clinical and radiological disease activity in MS. Although the causality between disease activity in MS and abnormalities in lipid metabolism has not yet been elucidated, we suggest that advances in this field of research have the potential to improve understanding of MS pathophysiology and the identification of new treatment targets and strategies.
Keywords: MRI, multiple sclerosis; Lipoproteins, HDL; HDL; LXR; lipoproteiny HDL; Cholesterol; LDL; cholesterol; lipoproteiny LDL; Oxysterols; lidé; Lipoproteins, LDL; roztroušená skleróza; metabolismus lipidů; Humans; Multiple Sclerosis; Lipid Metabolism